Combining emissions trading and emissions taxes in a multi-objective world - Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2010)
The combination of emissions trading and emissions taxes is usually rejected as redundant or inefficient. This conclusion is based on the restrictive assumption that both policies are exclusively meant to control pollution. However, particularly taxes may pursue a variety of other policy objectives as well, such as raising fiscal revenues or promoting equity. Multiple objectives may justify multiple policies. In this case, welfare losses with respect to pollution control may be traded off by benefits from attaining other policy objectives. Consequently, pragmatic policy recommendations have to be based on an in-depth understanding of interactions in the policy mix. This article makes three contributions that are relevant in this respect. (1) The most important factors distorting pollution abatement under the policy mix are identified. This insight is required to estimate the actual extent of inefficiency in controlling pollution, and to compare it with benefits of attaining other objectives of the tax. (2) The policy mix is not only compared to the unrealistic ideal of an efficient single emissions trading scheme but also to a suboptimal heterogeneous emissions tax. It is shown that if the tax is required to address multiple policy objectives, the implementation of an emissions trading scheme in addition may in fact increase the efficiency of pollution control. (3) It is demonstrated that welfare losses can be minimized within a policy mix by modifying emissions trading design.
Keywords: H23; H32; Q58; 360; policy mix; emissions trading; emissions tax; efficiency; Emissionshandel; Ökosteuer; Policy-Mix; Wirtschaftspolitisches Ziel; Wohlfahrtseffekt; Theorie